Transition from low-threshold vocational education and training to work in Switzerland: Factors influencing objective and subjective career success - Claudia Hofmann; Xenia Müller; Annette Krauss; Kurt Häfeli (International Journal for Research in Vocational Education and Training (IJRVET), 2021)
Context: There are currently two low-threshold vocational education and training (VET) options in Switzerland for young people at risk: A two-year programme for a Federal VET certificate and a practical training programme designed for young people with special needs. In the present study, we looked at transitions from these programmes to the labour market. Possible influences on objective and subjective indicators of career success, such as social background, personal disposition, and training, were considered. Methods: Data were collected from 418 apprentices in the French- and German-speaking parts of Switzerland at three measurement points: t1, at the beginning of training; t2, upon completion of training; and t3, 10 months later. Participants responded to a written questionnaire. Findings: Ten months after completing their apprenticeships, the majority of participating young people were either employed or continuing their education. Results of the multinomial logistic and linear regressions showed a differentiated, rather than uniform, picture depending on the criteria for career success. The background factors of gender and school (9th grade) were associated with objective success after the apprenticeship ended but not with subjective career success (hypothesis 1). For the variables concerning person disposition and agency (hypothesis 2), we found two plausible associations: A positive attitude towards life helped with unemployment avoidance and a highly self-rated school performance was associated with later satisfaction. As predicted in hypothesis 3, situational factors related to the VET company and school showed a number of significant but sometimes weak associations with objective and subjective career success. Additionally, competencies and support of VET trainers related to continuance in the learned profession. Conclusions: The career development paths of young people are influenced by various background and personality factors, as well as the training situation. VET trainers should be aware of their crucial role and understand how their interventions affect apprentices' self-perceptions and perceptions of their learned professions, which consequently influence their motivations and career aspirations. The situation at the VET school (as a learning and social place) is equally important, especially because of the aim to increase permeability for further training. Young people not in employment, education or training (NEET) are of particular concern. Even though this group is smaller in Switzerland than in most other countries, a number of problematic symptoms can be detected during apprenticeship that point to the need for the prevention of a later NEET status.
urn:nbn:de:gbv:18-10-5563
Keywords: 330; Vocational Education and Training; VET; Special Education; Career Development; Outcomes of Education and Training; Employment